2017
DOI: 10.2334/josnusd.16-0127
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nonsurgical periodontal treatment on clinical periodontal variables and salivary resistin levels in obese Asians

Abstract: This study investigated changes in periodontal outcomes after nonsurgical periodontal treatment (NSPT) and evaluated associations of change in salivary resistin level with periodontal outcomes in obese Malaysians with chronic periodontitis. Sixty-two obese adults with chronic periodontitis were randomly divided into a test group (n = 31), which received NSPT, and a control group (n = 31), which received no treatment. Plaque score (PS), gingival bleeding index (GBI), probing pocket depth (PPD), and clinical att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 39 publications
2
31
2
2
Order By: Relevance
“…The overall kappa value for intra‐examiner reliability was 0.91. The following parameters were assessed: full‐mouth PI, BOP, probing depth (4‐6 mm and >6 mm) and clinical attachment loss (in mm) on all maxillary and mandibular teeth except third molars …”
Section: Methodsmentioning
confidence: 99%
“…The overall kappa value for intra‐examiner reliability was 0.91. The following parameters were assessed: full‐mouth PI, BOP, probing depth (4‐6 mm and >6 mm) and clinical attachment loss (in mm) on all maxillary and mandibular teeth except third molars …”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that under oral and systemic pathological conditions, such as periodontitis and acquired immune deficiency syndrome, respectively saliva demonstrates altered protein levels (including cytokines and immunoglobulins). [1][2][3] These proteins act as potential biomarkers that could facilitate the screening of oral and systemic inflammatory diseases. 4 Another advantage of using saliva for screening purposes is that saliva can be collected noninvasively using simple methods such as expectoration.…”
Section: Discussionmentioning
confidence: 99%
“…Saliva is a complex biological fluid that is essential for physiological functions including mastication, deglutition, and digestion. Studies have shown that under oral and systemic pathological conditions, such as periodontitis and acquired immune deficiency syndrome, respectively saliva demonstrates altered protein levels (including cytokines and immunoglobulins) . These proteins act as potential biomarkers that could facilitate the screening of oral and systemic inflammatory diseases .…”
Section: Introductionmentioning
confidence: 99%
“…Periodontal tedavi sonrası resistin seviyesinin değer-lendirildiği kısıtlı sayıda çalışma mevcuttur (Tablo 2). [42][43][44][45][46] Tablo 2. Başlangıç periodontal tedavi sonrası resistin seviyesini değerlendiren çalışmalar.…”
Section: Resim 1 Periodontitis Tip 2 Diabetes Mellitus Ve Insülin Dunclassified
“…Tükürük resistin seviyesinin 12. haftada azaldığı bildirilmiştir. 46 Meydana gelen bu azalmayı takip döneminde lokal enflamasyonu azaltmasında ilişkilendirilmiştir. Sonuç olarak, enflamatuvar süreçte resistin önemli bir rol oynamaktadır.…”
Section: Resim 1 Periodontitis Tip 2 Diabetes Mellitus Ve Insülin Dunclassified